2016
DOI: 10.3329/bjog.v28i2.30093
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies and Maternal Outcome of Placenta Accreta

Abstract: Objectives: To find out the proportion and maternal outcome of placenta accreta.Materials and Methods: Total 10579 deliveries were served during January 2013 to 31st December 2013 in the Department of Obstetrics and Gynecology of Addin Women Medical College Hospital, Dhaka. All patients who needed postpartum or cesarean hysterectomy for postpartum hemorrhage and diagnosed as placenta accreta after postpartum hysterectomy were included for the study. Among them who were antentally diagnosed as placenta previa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…In this study common indications were previous section 16%, foetal distress 15%, obstructed labour 14%, pre-eclampsia and eclampsia 12%. Previous section constitute 20.41% in another study in our country Chowdhury and Begum et al [18] Present study findings correlate with it. Repeat sections constitute the commonest indication for LSCS in most other countries.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study common indications were previous section 16%, foetal distress 15%, obstructed labour 14%, pre-eclampsia and eclampsia 12%. Previous section constitute 20.41% in another study in our country Chowdhury and Begum et al [18] Present study findings correlate with it. Repeat sections constitute the commonest indication for LSCS in most other countries.…”
Section: Discussionsupporting
confidence: 79%
“…Begum et al [10] found that 77.0% came from low socioeconomic status. Begum et al; Rouf et al; Ara et al and Begum et al [15][16][17][18] ] mentioned that eclampsia is a disease of lower class who do not have basic education, do not receive ANC, do not seek health advice & present only in grave form of the disease. Yaqub et al [13] found in their study that 56% cases of eclampsia observed with women who conceived first time i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted at a local hospital in the same city quoted its incidence as 4.7 per 1000 deliveries 4 . Similar studies done in India and Bangladesh have shown its incidence of 1.2 and 2 per 1000 deliveries respectively 5,6 .…”
Section: Discussionsupporting
confidence: 64%
“…Hysterectomy in a Tertiary Level Hospital In Bangladesh, haemorrhage is still the leading cause of maternal mortality [20][21][22] . The diagnosis of placenta accreta is made on obstetric ultrasonography, usually in the second and third trimester of pregnancy 23 . Sometimes, patients present with acute emergency that is mild to severe antepartum haemorrhage with features of shock without having any investigations.…”
Section: Outcome Of Placenta Percreta Management By Planned Peripartummentioning
confidence: 99%